Degree of approximation of Conjugate Series of a Fourier Series by (E,r)(N,p,q) Means (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper a theorem on degree of approximation of a function f Lip ? by product Summability(E,r)(N,p,q)of conjugate series of Fourier series associated with f, has been established.